Canakinumab reverses overexpression of inflammatory response genes in tumour necrosis factor receptor-associated periodic syndrome. Issue 1 (29th July 2016) - Torene, Rebecca; Nirmala, Nanguneri; Obici, Laura; Cattalini, Marco; Tormey, Vincent; Caorsi, Roberta; Starck-Schwertz, Sandrine; Letzkus, Martin; Hartmann, Nicole; Abrams, Ken; Lachmann, Helen; Gattorno, Marco
Abstract : Objective: To explore whether gene expression profiling can identify a molecular mechanism for the clinical benefit of canakinumab treatment in patents with tumour necrosis factor receptor-associated periodic syndrome (TRAPS). Methods: Blood samples were collected from 20 patients with active TRAPS who received canakinumab 150 mg every 4 weeks for 4 months in an open-label proof-of-concept phase II study, and from 20 aged-matched healthy volunteers. Gene expression levels were evaluated in whole blood samples by microarray analysis for arrays passing quality control checks. Results: Patients with TRAPS exhibited a gene expression signature in blood that differed from that in healthy volunteers. Upon treatment with canakinumab, many genes relevant to disease pathogenesis moved towards levels seen in the healthy volunteers. Canakinumab downregulated the TRAPS-causing gene (TNF super family receptor 1A ( TNFRSF1A )), the drug-target gene (interleukin ( IL ) -1B ) and other inflammation-related genes (eg, MAPK14 ). In addition, several inflammation-related pathways were evident among the differentially expressed genes. Canakinumab treatment reduced neutrophil counts, but the observed expression differences remained after correction for this. Conclusions: These gene expression data support a model in which canakinumab produces clinical benefit in TRAPS by increasing neutrophil apoptosis and reducing pro-inflammatory signals resulting from the inhibition of IL-1β. Notably, treatment normalised the overexpression of TNFRSF1A, suggesting that canakinumab has a direct impact on the main pathogenic mechanism in TRAPS. Trial registration number: NCT01242813.